Congenital left atrial appendage aneurysm: Atypical presentation - Mehdi Bamous; Mahdi Aithoussa; Ayoub Abetti; Abdelatif Boulahya (Wolters Kluwer Medknow Publications, 2017)
Congenital left atrial appendage aneurysm is a rare condition caused by dysplasia of the atrial muscles. We report a case of a 14-year-old boy, with a 5-month history of cough and in sinus rhythm. Transthoracic echocardiography and computerized tomographic angiography confirmed the aneurysm of the left atrial appendage which was resected through median sternotomy on cardiopulmonary bypass. This case is presented not only for its rarity but also for its atypical clinical presentation.